The Analysis of the Influence of Foreign Direct Investment and Domestic Direct Investment on Economic Growth in the Province of Bengkulu - Reli Sapitri; Abdullah Abdullah (UNIVED Press, 2024)
Investment is one of the diverse factors influencing the economic growth of a region. This research focuses on foreign and domestic direct investment in the districts and cities of the Bengkulu Province. The aim of this study is to make a significant contribution to improving the welfare of the community in this region. Additionally, the research provides guidance to policymakers in developing effective investment strategies. The method employed in this research is quantitative, utilizing the EViews software. The study uses the values of the total Foreign Direct Investment (FDI) and Domestic Direct Investment (DDI) collected from the Bengkulu Province's Central Bureau of Statistics (BPS). It was found that FDI does not have a significant impact on economic growth, in contrast to DDI, which significantly contributes positively to the economic growth of the Bengkulu Province. It is important to note that this research was conducted in a single region and only utilized two independent variables.